Knowledge and practice of design in the training of professionals in non-concurrent areas of design in public universities in Bogotá, Colombia (2018)
This research article deals with the purpose of configuring a pattern, knowledge and practice of what is understood as design activities from its dimensions: thought, design methodology and aesthetic dimensions, within higher education teaching areas not associated to design professions. This research seeks to identify how teaching processes are understood and executed around the resolution of weakly structures problems in some other areas of knowledge and academic contexts of higher education in public universities in Bogotá, Colombia. Consequently, to achieve this goal, a description, characterization and analysis of the curricular contents that these universities follow in the creation of topics is developed by identifying their origins, bases, methods, and their reason of being in the formation of professionals in sciences, engineering and humanities. As a result, the main finding was to show how in the professional training programs analyzed, the thinking, method and aesthetics of the disciplinary field of design are applied, which allows to establish the levels of influence of this field of knowledge in non-concurrent areas of the design. As a result, the main finding on this study was to show how in the professional training programs analyzed, the thinking, method and aesthetics of the disciplinary field are applied, which allows to establish the levels of influence of this field of knowledge in non-concurrent areas of design.